Early Childhood Development in the Context of the Family: The Case of Child Marriage. Issue 4 (1st October 2016) - Wodon, Quentin
Abstract: Early childhood is a critical period in a child's development. Poor conditions early in life affect not only children's physical growth, but also their brain development and capabilities, with lasting consequences in adulthood. A child's family is the first and most important support system to ensure healthy growth and development. This also means that when the family and especially the mother is vulnerable, this can have lasting negative consequences for young children. This article illustrates the impact that family conditions can have on early childhood development by considering the specific case of child marriage, defined as a girl marrying before the age of 18, as well as early childbirth, defined as a girl having a child before the age of 18, itself in most cases a consequence of child marriage. The article also discusses interventions that could help in reducing both the likelihood of child marriage and its intergenerational impacts on young children.